The making and unmaking of whiteness - Brander Rasmussen, Birgit 1968-; Klinenberg, Eric 1970-; Nexica, Irene J.; Wray, Matt 1964- (Duke University Press, 2012)
Universal freckle, or how I learned to be white / Dalton Conley -- "The souls of white folks" / Mab Segrest -- The mirage of an unmarked whiteness / Ruth Frankenberg -- White racial projects / Howard Winant -- The "Morphing" properties of whiteness / Troy Duster -- "White devils" talk back : what antiracists can learn from whites in Detroit / John Hartigan Jr. -- Transnational configurations of desire : the nation and its white closets / Jasbir Kaur Puar -- Perfidious Albion : whiteness and the international imagination / Vron Ware -- The new liberalism in America : identity politics in the "vital center" / Eric Lott -- How gay stays white and what kind of white it stays / Allan Bérubé -- (E)racism : emerging practices of antiracist organizations / Michael Omi -- Moving from guilt to action : antiracist organizing and the concept of "whiteness" for activism and the academy / William Aal
Auf der Landingpage: "Bringing together new articles and essays from the controversial Berkeley conference of the same name, The Making and Unmaking of Whiteness ..."
Informationen wurden der Landingpage entnommen, da weder Titelblatt noch Impressum vorhanden sind (Duke University Press)
Keywords: Whites / Congresses / Race identity / United States; Race awareness / Congresses / United States; Racism / Congresses / United States; Social classes / Congresses / United States; Ethnische Beziehungen; Schwarze; USA; Konferenzschrift -- 1997 -- Berkeley Calif.